143 Effect of siponimod on disability progression measured by ambulation score: post hoc analysis of EXPAND. Issue 9 (12th August 2022) - D'Souza, Marcus; Giovannoni, Gavin; Vermersch, Patrick; Maca, Jeff; Ansari, Soudeh; Karlsson, Goeril; Piani-Meier, Daniele; Kappos, Ludwig
Abstract : Background: In the Phase 3 EXPAND study, siponimod reduced the Neurostatus-EDSS-measured risk of 3/6-month (M) confirmed disability progression versus placebo by 21%/26%, with more pronounced effects (31%/37%) in active SPMS (aSPMS). Here we evaluated the contribution of the Ambulation Score (AS) to measuring siponimod's effect on disability progression. Design/Methods: This post-hoc analysis included the overall population (OP); siponimod/placebo n=1099/546) and aSPMS/non-active (naSPMS) patients (siponimod, n=516/557; placebo, n=263/270). Outcomes included change from baseline in Neurostatus-EDSS/AS, time-to-first worsening on AS (3M/6M confirmed worsening [3M/6MCW]) by ≥1/≥2-points and categorical analysis (proportion of patients with 3M/6MCW or confirmed improvement [CI] by ≥1-point during the core study [median(range): 21(0.2–37.0) M]). Results: In the OP, the Neurostatus-EDSS, and more prominently, AS change from baseline, favored siponimod versus placebo at all visits (M6-M30); most pronounced at M18 (EDSS: 0.13 versus 0.23;p=0.003; AS: 0.50 versus 0.81;p=0.001). Siponimod significantly reduced the risk of 3MCW (≥1-point, HR=0.78, p=0.0046; ≥2-point, 0.71, p=0.0007) and 6MCW in AS (≥1 point, 0.74, p=0.0023).In aSPMS, pronounced effects were observed in 3MCW (≥1-point, HR=0.68, p=0.002; ≥2-point, 0.60, p=0.0005); 6MCW (≥1-point, HR=0.63, p=0.0007), with fewer patients worsening/more improving on siponimod and a trend for fewer patients worsening in naSPMS. Conclusions: More pronounced effects on the Neurostatus-EDSS and AS were observed in aSPMS. Funding: Novartis Pharma AG, Basel, Switzerland.